Transmitting Faith in the Republic Muslim Schooling in Modern Plural France - Ferrara, Carol A. (2018)
This article explores and analyzes private Muslim schooling in France using ethnographic research performed in 2013-2014 in Lille-, Lyon-, and Paris-based Muslim schools. The article discusses the course content and the interpretations of Islam that are taught, demonstrating how French republican values are fused together with Islam to promote a specific brand of French Muslim citizenship and identity. I argue that Muslim schools should be seen as part of the process of the normalization of Muslim-based civic engagement and that they represent a particular response to France's new plurality that reinterprets the boundaries of "French" and "Muslim."